Comparative analysis in the perception of performance: integration of the dimensions of competition in the company of goods and services" (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2011)
For managers of service companies, it is difficult to accept that they can apply in their businesses, operations management techniques used in real companies, it is common to say that how to manage goods and services is different, but the direction of operations has included concepts applied in goods, also to services. To make an analysis of this situation, this study reflects the views of asset managers and service managers about the attention given to the development dimension of competition (quality, flexibility and cost) and the relationship with profitability in their respective businesses. We surveyed a total of 150 goods companies and 108 services, the research results are given separate treatment and finally compared to determine the similarity or difference between the opinion of the directors of goods and services respectively. If comparing the results, they are similar indicates that the administration of goods or services must be performed using the same forms of work and if you give us a different result tells us that must be managed differently. The final result shows us that there is a positive influence between the integration of the dimensions of competition and profitability, as well as the similarity in the way of conceptualizing aspects relating to the dimensions of the competition by showing the similarity in requirements management systems for both sectors.
Keywords: services; assets; profitability; size of the competition